Nursing care: recognition in the Spanish stamps - Antonio Manuel Ballesteros Álvaro (Universidad de Alicante, 2012)
The first post stamp in Spain was issued January 1st, 1850. Since then up to the present day, paramount people, celebrities, events... worth to be recognised and remembered world wide, have been given a public recognition in the stamp. Our work here tries to analyse 150 years of Spanish stamps, since the Nursing and caring point of view.